Early Developmental Destruction of Terminals in the Striatal Target Induces Apoptosis in Dopamine Neurons of the Substantia Nigra - Marti, Maria J. (J Neurosci, 1997)
Many developing neural systems with peripheral projections depend on their target for trophic support during a critical period of natural cell death. Much less is known about central systems. That dopaminergic neurons of the substantia nigra may depend on their target, the striatum, during development is suggested by the presence of a natural apoptotic cell death event in these neurons that can be augmented by an early developmental axon-sparing striatal injury. To further assess the target dependence of these neurons, we have used the selective neurotoxin 6-hydroxydopamine to lesion their terminals within the striatum during development, while sparing intrinsic striatal target neurons. This lesion results in an induction of apoptotic cell death in phenotypically defined dopaminergic neurons that appears on the third postlesion day and persists until the tenth. This inducibility of cell death is dependent on developmental age: it is most marked before postnatal day (PND) 14. As late as PND42, inducibility is still detectable but much less so. In addition, at day 42 the morphology of cell death changes and becomes nonapoptotic in some cells. We conclude that terminal injury during a critical period of postnatal development, like axon-sparing target injury, induces augmented apoptotic death in mesencephalic dopaminergic neurons. These results suggest that these neurons have a period of target dependence. Regulation of this dependence is likely to influence the mature adult number of dopaminergic neurons.